First record of Pellonyssus gorgasi Yunker & Radovsky, 1966 (Mesostigmata: Macronyssidae) in Cuba and a new host association - de la Torre Santana, Pedro E.; Bassini-Silva, Ricardo [UNESP]; Dowling, A. P.G.; Armas, Luis F. (Taylor & Francis, 2022)
The mite Pellonyssus gorgasi Yunker & Radovsky is recorded for the first time in Cuba, based on several specimens collected on a young Cuban Emerald, Riccordia ricordii ricordii (Gervais) (Apodiformes: Trochilidae) and in its nest from San Antonio de los Baños, Artemisa Province. In this study, R. r. ricordii represents a new host-association for P. gorgasi, whereas the genus Pellonyssus is also recorded for the first time in Cuba.
Keywords: Cuban Emerald; ectoparasite; hummingbird; mite; Riccordia ricordii ricordii; West Indies